The influence of a changing environment on the breeding biology and diet of Kelp Gulls (Larus dominicanus vetula) in Plettenberg Bay, South Africa - Witteveen, Minke (Percy FitzPatrick Institute of African Ornithology, 2015)
We live in a constantly changing world, where recent human-induced changes and climate change affect virtually every component of the Earth's surface and systems. Coastal ecosystems are particularly at risk, as one of the most utilised and urbanised of natural systems worldwide, as well as being at risk from sea level rise. This will degrade or even destroy many feeding and breeding sites. Those species colonising new habitats in an attempt to escape rising sea level and climate change related threats, will be competing for space with the growing human population and urbanisation. Although 97 of 346 seabird species (28%) are globally threatened, 57 (17%) have increasing populations, including 17 gulls (Larinae). The Kelp Gull Larus dominicanus is a cosmopolitan species with an increasing population worldwide. Kelp Gulls in southern Africa L. d. vetula are one of 15 seabird species that breed in the region, and one of only five breeding seabirds listed as Least Concern in the region. Three Kelp Gull breeding colonies in Plettenberg Bay, Western Cape, were surveyed to provide an updated count for this area. A combination of direct counts and the trial use of an unmanned aerial vehicle (UAV),were used as methods of counting nests. The direct monitoring of nests allowed for the effect of different microhabitats on the breeding performance of Kelp Gulls to be investigated, which has implications for their ability to adapt to future habitat changes. The importance of anthropogenic food items in the diet of Kelp Gulls breeding in Plettenberg Bay was explored through the use of regurgitated pellets of indigestible matter, and chick regurgitations, and how this is reflected in the time spent in various areas as shown by GPS loggers and point counts in urban areas. Another aspect of the urban adaptation of Kelp Gulls is the incorporation of anthropogenic debris in their nests, which was examined at eight breeding colonies throughout the Western Cape.